New antimicrobial biomaterials based on recombinant spider silks - Beinarovica, Jolanta (2022)
Spider silk is a protein-based material with exceptional mechanical properties together with low immunogenicity and pyrogenicity which makes it useful in biomedical applications. The cannibalistic and highly territorial nature of most spiders prevents high-density farming; therefore, the availability of their silk in a usable form is very limited. Recombinant production of silks is explored as an alternative mean of production. This study uses two miniature recombinant silk proteins (mini-spidroins) with distinct biochemical nature -NT2RepCT and 4RepCT - to create new materials for drug delivery.